Food safety in Bangladesh: A microbiological perspective (Stamford Journal of Microbiology, 2017)
Bangladesh has long been facing problems associated with microbiological contamination of varieties foods due to the lack of awareness on hygiene followed by the defective legislative action. Manifestation of microbial prevalence in different foods bring about vital information on food safety as well as may envisage on the further intoxication caused by the prevailing microorganisms. Although a few extent of food inspection is apparently in some of the governmental regulatory bodies; however, the mass population is still suffering from a number of food borne illness. Present review partially focused on the microbiological regulation of the foods in Bangladesh and discussed the possible remedies for the maintenance of food safety.Stamford Journal of Microbiology, Vol.6(1) 2016: 1-6